2011
DOI: 10.1104/pp.111.175380
|View full text |Cite
|
Sign up to set email alerts
|

Sugar Signaling in Root Responses to Low Phosphorus Availability

Abstract: Over the last decade, major advances have been made in our understanding of how plants sense, signal, and respond to soil phosphorus (P) availability (Amtmann et al

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
114
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(117 citation statements)
references
References 107 publications
(162 reference statements)
2
114
1
Order By: Relevance
“…The enhanced PM H + -ATPase activity, increased organic acid exudation, and augmented root biomass displayed by 35Sp:AVP1 or 35Sp:AVP1D plants are consistent with an increased sugar supply, as described by Hammond and White (2011) and documented in genetically modified ZmPTF1 maize plants (Li et al, 2011). Of note, an elegant stem-girdling experiment showed that white lupin required phloem sugar transport for the expression of Pi deficiency-induced genes in cluster roots (Liu et al, 2005).…”
Section: The Sugar and Phosphate Connectionmentioning
confidence: 73%
“…The enhanced PM H + -ATPase activity, increased organic acid exudation, and augmented root biomass displayed by 35Sp:AVP1 or 35Sp:AVP1D plants are consistent with an increased sugar supply, as described by Hammond and White (2011) and documented in genetically modified ZmPTF1 maize plants (Li et al, 2011). Of note, an elegant stem-girdling experiment showed that white lupin required phloem sugar transport for the expression of Pi deficiency-induced genes in cluster roots (Liu et al, 2005).…”
Section: The Sugar and Phosphate Connectionmentioning
confidence: 73%
“…Under P starvation, more sucrose is allocated to the root system, allowing extensive growth and changing the shoot-root ratio for biomass in most plants [37]. However, sucrose is not only an energy source, but also a signalling compound (e.g., [38,39]). Two reports have shown that in Lupinus albus cluster roots are formed in the presence of sufficient P supply when sucrose is supplied to the medium [34,40].…”
Section: The Role Of Phytohormones and Sugars In Cluster-root Formationmentioning
confidence: 99%
“…Sugars synthesized in the green parts of plants are known to have important roles as signaling molecules in addition to their metabolic functions (16)(17)(18), for example, acting as a systemic signal for promoting root development in response to phosphorus starvation (19). We tested the hypothesis that the light stimulus emerging in the cotyledons and transmitted to the root is photosynthetically produced sugar.…”
mentioning
confidence: 99%